2018
DOI: 10.1210/en.2018-00039
|View full text |Cite
|
Sign up to set email alerts
|

Local Estrogen Synthesis Regulates Parallel Fiber–Purkinje Cell Neurotransmission Within the Cerebellar Cortex

Abstract: Estrogens affect cerebellar activity and cerebellum-based behaviors. Within the adult rodent cerebellum, the best-characterized action of estradiol is to enhance glutamatergic signaling. However, the mechanisms by which estradiol promotes glutamatergic neurotransmission remain unknown. Within the mouse cerebellum, we found that estrogen receptor activation of metabotropic glutamate receptor type 1a strongly enhances neurotransmission at the parallel fiber-Purkinje cell synapse. The blockade of local estrogen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…Although 17-β-estradiol inhibits T and B cell development, it enhances B cell function in ERα-dependent manner, involving both genomic and non-genomic ER signaling in B lymphocytes [ 39 , 40 ]. Moreover, the brain of both sexes is a major target of estradiol and a site of estrogen synthesis [ 41 , 42 ]. ERβ is a dominant ER subtype in the adult cerebellum.…”
Section: Expression Of Er In Normal Tissuesmentioning
confidence: 99%
“…Although 17-β-estradiol inhibits T and B cell development, it enhances B cell function in ERα-dependent manner, involving both genomic and non-genomic ER signaling in B lymphocytes [ 39 , 40 ]. Moreover, the brain of both sexes is a major target of estradiol and a site of estrogen synthesis [ 41 , 42 ]. ERβ is a dominant ER subtype in the adult cerebellum.…”
Section: Expression Of Er In Normal Tissuesmentioning
confidence: 99%
“…Nevertheless, the age-related maintenance of a low level of aromatase expression in the cerebellum seems to have a cardinal physiological significance in the contribution of controlling the cerebellar function. Recent reports showed that nE2 synthesis rapidly influences the glutamatergic transmission between the parallel fibers and Purkinje cells in the cerebellar cortex and acutely impact cerebellar dependent behaviors in adult rodents [39,40,74,87]. Furthermore, the high level of estrogen receptors found in the cerebellum of adults is supportive of cerebellar responsiveness even to a minute and localized nE2 synthesis [88][89][90].…”
Section: The Effectiveness Of the De Novo Synthesized Estradiol In Ramentioning
confidence: 99%
“…Experiments conducted in the brainstem and cerebellum indicate that despite the supposed low synthesis in the experimental models used, nE2 may contribute to rapidly modulating neurotransmission via dynamic change of its availability at a synaptic level [38][39][40][41][42]. It has already been demonstrated that modifications in local estradiol synthesis may be achieved by changes in aromatase activity.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, estrogen was shown to increase the expression of glutamate receptor GluR1 and increase spine density and glutamatergic synapse formation in both PFC and superficial superior colliculus neurons (Khan, Dhandapani, Zhang, & Brann, ). Further, estrogen has been demonstrated to regulate neurotransmission in the cerebellum and increase glutamatergic synaptic transmission in the hippocampus, but through different mechanisms in males and females (Hedges et al, ; Oberlander & Woolley, ). This sex‐specific difference highlights how the same functional endpoint can be achieved in a cell through different pathways, and that the functional endpoint can be perturbed differently based on sex.…”
Section: Introductionmentioning
confidence: 99%